Solute Carrier Family 30 Member 8 Gene 807C/T Polymorphism and Type 2 Diabetes Mellitus in the Chinese Population: A Meta-Analysis Including 6,942 Subjects - Li, Yan-Yan; Lu, Xin-Zheng; Wang, Hui; Yang, Xin-Xing; Geng, Hong-Yu; Gong, Ge; Zhan, Yi-Yang; Kim, Hyun Jun; Yang, Zhi-Jian (Frontiers in Endocrinology, 2018)
Background: Although Solute carrier family 30 (zinc transporter) member 8 (SLC30A8) gene 807C/T polymorphism is associated with an increased risk of Type 2 Diabetes Mellitus (T2DM) risk, there remains some inconsistency between individual studies . Objective: The aim of the study is to explore the relationship between SLC30A8 gene 807C/T polymorphism and T2DM in the Chinese population. Methods: The current meta-analysis compiles and analyzes the data of 6,942 participants from 10 studies independent studies. Either a fixed or random-effects model was adopted to evaluate the pooled odds ratio (ORs) and the corresponding 95% confidence interval (95% CI). Results: A significant association between SLC30A8 gene 807C/T polymorphism and T2DM was found in the Chinese population under allelic (OR: 0.85, 95% CI: 0.80-0.91, P = 7.42×10-7), recessive (OR: 0.52, 95% CI: 0.38-0.72, P = 8.49×10-5), dominant (OR: 2.40, 95% CI: 1.68-3.41, P =1.30×10-6), homozygous (OR: 0.52, 95% CI: 0.40-0.67, P = 2.90×10-7), heterozygous (OR: 0.79, 95% CI: 0.71-0.88, P = 1.63×10-5), and additive genetic models (OR: 0.73, 95% CI: 0.64-0.83, P = 7.05×10-7). Conclusions: SLC30A8 gene 807C/T polymorphism was significantly associated with an increased T2DM risk in the Chinese population. Therefore, individuals of Chinese descent with the C allele of SLC30A8 gene 807C/T polymorphism may be more susceptible to developing T2DM, while individuals with the T allele may be protected against T2DM.